Nursing of a patient with chronic gastritis complicated with anxiety and depression treated by Bian-stone hot ironing-massage and Chinese herbal medicine penetration combined with music-guided imagination therapy (砭石熨摩中药透入法联合引导性音乐想象治疗1例慢性胃炎伴焦虑抑郁患者的护理体会) - DU Litao (杜丽涛); HUANG Yanping (黄砚萍); ZHANG Man (张曼); DONG Shuo (董硕); SHI Yanhui (石彦会); DONG Chunfang (董春芳) (中西医结合护理)
This paper summarized the nursing experience of a patient with chronic gastritis complicated with anxiety treated by Bian-stone hot ironing-massage and Chinese herbal medicine penetration combined with music-guided imagination therapy. The music-guided imagination therapy was used to relieve patient’s negative emotions. Bian-stone hot ironing-massage and Chinese herbal medicine penetration were carried out to relieve the gastrointestinal symptoms of the patients. These two TCM technologies were complementary in the treatment of chronic gastritis complicated with anxiety and depression. (本文总结1例慢性胃炎伴焦虑抑郁患者应用砭石熨摩中药透入法联合引导性音乐想象的护理体会。通过引导性音乐想象技术缓解患者不良情绪, 并运用砭石熨摩中药透入法对患者胃肠症状进行干预。砭石熨摩中药透入和引导性音乐想象技术联合应用, 相得益彰, 起到身心同治的效果, 进一步改善患者胃肠症状。)